2018
DOI: 10.5335/rfo.v22i3.7733
|View full text |Cite
|
Sign up to set email alerts
|

Linear polymerization shrinkage of Bulk Fill resins

Abstract: (3, 6, 9, and 12 o'clock)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…However, the other bulk-fill flowable composite (GBI) had similar shrinkage to conventional flowable composite, which can be related to these composites' content of resin matrix. XB had the lowest shrinkage among flowable composites (3.3%), similarly, T. C. Correia et al (2017) reported in their study that XB caused the lowest marginal gap.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…However, the other bulk-fill flowable composite (GBI) had similar shrinkage to conventional flowable composite, which can be related to these composites' content of resin matrix. XB had the lowest shrinkage among flowable composites (3.3%), similarly, T. C. Correia et al (2017) reported in their study that XB caused the lowest marginal gap.…”
Section: Resultssupporting
confidence: 61%
“…Using flowable bulk‐fill composites has the advantage of better material adjustment to the cavity walls and polymerization stress reduction due to low modulus of elasticity (T. C. Correia et al, 2017 ; Soares et al, 2017 ). It was reported that flowable bulk‐fill composites had better marginal seals compared to packable bulk‐fill composites (Orłowski et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%